Relação entre a produção primária epilítica e a estrutura populacional de Neritina zebra (Mollusca: Gastropoda) na Ilha de Mosqueiro, Belém-PA - SOUZA, Débora da Silva (2018)
The rocky shores contain a large number of species of economic and ecological importance. In this environment, the high productivity in the substrate gives an appropriate condition for the settlement of benthic species and the fixation of sessile organisms. Primary production is performed by the microphytobenthic component of biofilm epilithic. The objective of this work was to evaluate the temporal variation of the Neritina zebra gastropod and its relationships with the primary epilithic biomass on the consolidated substrate of the beaches of Paraiso, Farol and Grande da Ilha de Mosqueiro-Pará. The samplings occurred in the months of May and October of 2014 and 2017, corresponding to months of the rainy and dry period, respectively. The densities of recruits, intermediates and adults were estimated to measure the influence of different size classes on biofilm availability. For the density samples, 25 x 25 cm square samplers were used and 10 replicates were made on each beach, and for the samples destined for chlorophyll-a extraction, used as an indirect measure of the primary production, fragments of rocks of approximately 3 x 3 cm. The biomass primary of the consolidated substrate of the Mosqueiro-PA intertidal shows higher production of the epileptic biofilm in the dry period and is related to the lower densities of Neritina zebra. The recruitment of individuals of Neritina zebra occurs in the rainy season and presents interannual variation. The relationship between the class of intermediates and the concentration of chlorophyll a has a negative tendency, ie, the higher densities of this class of size are associated with the lower rates of chl-a. Thus, understanding the relationships between different size classes over primary production is crucial to understanding the mechanisms involved in population control.